First, try to see if you can cancel out any of the variables by adding the equations.
4x+2y-1 also equals 4x+2y=1
(4x+2y=1)(2) = 8x+4y=2
now, add the two equations and see the y cancel out.
2x-4y=2
8x+4y=2
10x=4
x=4/10=2/5
Plug this number back into the equation (any of those two) and find y.
Solve the system by addition 2x-4y=7,4x+2y-1 can show one show me how to do this.
3 answers
i still do see how you got that answer i got 2x-4y=7 ,4x+2y=-1. 6x+6y=6 isn't that how you do it please help understand better
T.T
the purpose oft using addition here is to add them in such a way so that one of the variables will cancel out
leave the first equation alone
2x-4y=7, multiply the second by 2
8x+4y=-2, now add them
10x + 0 = 5
x = 1/2
back in the first....
2(1/2)-4y=7
1-4y=7
-4y=6
y=-3/2
You just added them to get 6x+6y=6
Even though that new equation is valid and true it gets you nowhere.
the purpose oft using addition here is to add them in such a way so that one of the variables will cancel out
leave the first equation alone
2x-4y=7, multiply the second by 2
8x+4y=-2, now add them
10x + 0 = 5
x = 1/2
back in the first....
2(1/2)-4y=7
1-4y=7
-4y=6
y=-3/2
You just added them to get 6x+6y=6
Even though that new equation is valid and true it gets you nowhere.